2018
DOI: 10.1039/c8sm02129e
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle wettability on the stick-slip motion of the contact line

Abstract: Contact line dynamics and deposition pattern of a colloidal drop are strong functions of the particle wettability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…Such nonadhered crystals may move with the contact line as it recedes. Such an effect has also been observed in experiments for colloidal solutions as a function of the particle surface tension …”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Such nonadhered crystals may move with the contact line as it recedes. Such an effect has also been observed in experiments for colloidal solutions as a function of the particle surface tension …”
Section: Discussionsupporting
confidence: 58%
“…Such an effect has also been observed in experiments for colloidal solutions as a function of the particle surface tension. 24 We have seen that crystalline patterns differ from colloidal patterns deposited from an evaporating drop under the same conditions and have demonstrated that area localization is correlated with the supersaturation (and therefore the nucleation barrier) at which crystals begin to form. We now briefly consider the hypothesis that saline-induced convection, which has been previously shown to strongly alter the interior flow of the drop, 29,30,37 influences these results.…”
Section: ■ Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Multiring pattern has been explained in previous works to be the result of stick‐slip motion of the contact line. [ 49 51 ] The broader and thicker ring at the outer edge could be attributed to convection flow towards the droplet contact line in order to replace the evaporated liquid at the border and consequently deposition of more solute dyes in that region. Such migration is accelerated with the influence of well‐known Marangoni flow inside the droplet, [ 52 ] specifically with the presence of poly(vinyl alcohol) (PVA) in this study acting as a surfactant.…”
Section: Resultsmentioning
confidence: 99%